2012
DOI: 10.1016/j.jcrs.2012.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial microincision cataract surgery versus conventional coaxial cataract surgery: Metaanalysis of randomized controlled trials

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 38 publications
3
23
0
1
Order By: Relevance
“…A meta-analysis of 11 RCTs, Yu 2012, evaluated the outcomes of B-MICS versus standard phacoemulsification and showed CDE and phacoemulsification time to be significantly less in the B-MICS group, which is consistent with our review. However, their review showed less SIA in the B-MICS group, which is not consistent with our review.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A meta-analysis of 11 RCTs, Yu 2012, evaluated the outcomes of B-MICS versus standard phacoemulsification and showed CDE and phacoemulsification time to be significantly less in the B-MICS group, which is consistent with our review. However, their review showed less SIA in the B-MICS group, which is not consistent with our review.…”
Section: Discussionsupporting
confidence: 87%
“…The difference in conclusions might be the result of the inclusion of different trials. We excluded eight RCTs that were included in Yu 2012; our reasons for exclusion are listed in the Characteristics of excluded studies table (Alio 2005; Crema 2007; Denoyer 2008; Kahraman 2007; Kurz 2006; Kurz 2009; Mencucci 2006). Also, Mao 2008, which was included in this review, was not included in Yu 2012.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important aspect because it has a direct impact on the functional effect after cataract surgery. 39 Additional activities which must be performed during Perfect Capsule TM device implantation into the anterior chamber can increase SIA. However, our study has not confirmed these doubts and the obtained results of UCVA and CDVA are in agreement with the reports of other comparative research studies.…”
Section: Discussionmentioning
confidence: 99%
“…7,10 Undoubtedly, the need of the application of 2.75 mm incision in the era of the decrease of the main incision during cataract surgery to 1.8-2.2 mm should be regarded as conservative. 39 On the other hand, silicone material from which the Perfect Capsule TM device is constructed enables further modification and adjustment to currently valid standards. Such a solution would also allow to reduce manipulations in the anterior chamber necessary for the system fixation to the anterior capsule and then to remove it from the anterior chamber in which we can seek the cause of greater relative loss of endothelial cells in comparison to the control group ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…It is now well established that smaller incisions tend to induce less SIA, at least in comparisons with standard 2.8 mm or 3.0 mm coaxial incisions and microincisional cataract surgery (MICS) involving incisions of 2.2 mm or smaller. [4][5][6][7] However, it is not only the initial incision size that matters. The incision architecture and integrity and the degree of incision stretching or manipulation during surgery can increase SIA even in MICS cases.…”
mentioning
confidence: 99%